The role of ball backspin alignment and variability in basketball shooting accuracy - Slegers, N.; Love, D. (Journal of Sports Sciences, 2022)
Interaction between the shooting hand and ball at the moment a basketball is released generates a three-dimensional backspin of the ball. This study is the first to investigate how characteristics of the backspin alignment and variability contribute to lateral shooting accuracy. Spin axis (SA) direction and backspin magnitude were measured on 25 shot attempts for 26 collegiate basketball players (male: n = 16, female: n = 10). The mean SA alignment, as viewed from the shooting hand side, was found to be tipped down and towards the target (p < 0.001). Standard deviations (SD) in the SA alignment were strong predictors of lateral accuracy (vertical SD: r = 0.80, p < 0.001, forward-backward SD: r = 0.51, p = 0.01), with variation in the vertical alignment being the best predictor. No significant correlation between mean SA misalignment and lateral accuracy was observed. However, intra-individual relationships between SA misalignment and lateral error revealed that individuals tended to have 0.17 degrees more misalignment for each cm of lateral error (p < 0.001, 95% CI: 0.24-0.09). These indicate that while an individual`s mean alignment may not predict lateral accuracy, improving one`s SA alignment and reducing alignment variability may increase lateral accuracy.